Immunohistochemical analysis of insulin‐like growth factor I, insulin‐like growth factor I receptor and insulin‐like growth factor II in endometriotic tissue and endometrium - Shiuh Y. Chang; Yat‐Sen Ho (Acta Obstetricia et Gynecologica Scandinavica)
Background. The purpose of this study was to investigate unprecedentedly immunohistochemical localization of insulin‐like growth factor I, insulin‐like growth factor I receptor and insulin‐like growth factor II in endometriotic tissue, and to compare staining intensity with that of endometrium obtained simultaneously. Methods. Endometriotic and corresponding endometrial tissue samples were obtained during operative laparoscopy from eighteen infertile patients for the problem of infertility. Semiquantitative scoring was used for analysis of results. Results. It was demonstrated that insulin‐like growth factor I and insulin‐like growth factor I receptor were present in both endometriotic and endometrial tissues. In contrast, there was little insulin‐like growth factor II present in either ectopic or eutopic endometrial tissue. For insulin‐like growth factor I and insulin‐like growth factor I receptor, the immunostaining score was similar between ectopic and eutopic endometrial tissues. There was no significant difference in immunostaining score between glandular epithelium and stromal cells. Conclusions, insulin‐like growth factor I and insulin‐like growth factor I receptor could be demonstrated immunohistochemically in both endometriotic and endometrial tissues.